Social Disparities in Dental Insurance and Annual Dental Visits Among Medically Insured Patients With Diabetes: the Diabetes Study of Northern California (DISTANCE) Survey - Moffet, Howard H. (Centers for Disease Control and Prevention, 2010)
INTRODUCTION: People with diabetes are at increased risk of periodontal disease and tooth loss. Healthy People 2010 set a goal that 71% or more of people with diabetes should have an annual dental exam. METHODS: We assessed dental insurance and annual dental visits among dentate respondents from the Diabetes Study of Northern California (DISTANCE) Survey cohort (N = 20,188), an ethnically stratified, random sample of patients with diabetes aged 30 to 75 years receiving medical care from Kaiser Permanente Northern California. We calculated predicted probabilities for an annual dental visit (PPADV) by using regression models that incorporated age, sex, education level, annual household income, and self-reported race/ethnicity, stratified by whether the respondent had dental insurance. RESULTS: Among 12,405 dentate patients, 9,257 (75%) had dental insurance. Annual dental visits were reported by 7,557 (82%) patients with dental insurance and 1,935 (61%) patients without dental insurance. The age-sex adjusted odds ratio for an annual dental visit was 2.66 (95% confidence interval, 2.33-3.03) for patients with dental insurance compared to those without dental insurance. For patients with dental insurance, the PPADV was 71% or more for all except those with the lowest household income. In contrast, for those without dental insurance, the PPADV was less than 71% for all except those with the most education or the highest income. We found some racial/ethnic subgroups were more likely than others to take advantage of dental insurance to have an annual dental visit. CONCLUSIONS: Patients with diabetes in this managed care population who lacked dental insurance failed to meet the Healthy People 2010 goal for an annual dental visit. An increased effort should be made to promote oral health among people with diabetes.